DIAGNOSTIC METHODOLOGY OF MUNICIPALITIES’ PERFORMANCE RESULTS - V.Y. VALYAVIN (Advanced Engineering Research)
Some aspects of the society’s estimation of municipalities based on their performance results as some complex of sociosystem elements are discussed.